Bro1 binds the Vps20 subunit of ESCRT‐III and promotes ESCRT‐III regulation by Doa4. (13th January 2022) - Buysse, Dalton; West, Matt; Leih, Mitchell; Odorizzi, Greg
Abstract: The budding of intralumenal vesicles (ILVs) at endosomes requires membrane scission by the ESCRT‐III complex. This step is negatively regulated in yeast by Doa4, the ubiquitin hydrolase that deubiquitinates transmembrane proteins sorted as cargoes into ILVs. Doa4 acts non‐enzymatically to inhibit ESCRT‐III membrane scission activity by directly binding the Snf7 subunit of ESCRT‐III. This interaction inhibits the remodeling/disassembly of Snf7 polymers required for the ILV membrane scission reaction. Thus, Doa4 is thought to have a structural role that delays ILV budding while it also functions enzymatically to deubiquitinate ILV cargoes. In this study, we show that Doa4 binding to Snf7 in vivo is antagonized by another ESCRT‐III subunit, Vps20. Doa4 is restricted from interacting with Snf7 in yeast expressing a mutant Vps20 allele that constitutively binds Doa4. This inhibitory effect of Vps20 is suppressed by overexpression of another ESCRT‐III‐associated protein, Bro1. We show that Bro1 binds directly to Vps20, suggesting that Bro1 has a central role in relieving the antagonistic relationship that Vps20 has toward Doa4. Abstract : In yeast, the Doa4 ubiquitin hydrolase deubiquitinates transmembrane proteins sorted as cargoes into intralumenal vesicles at endosomes. Doa4 also functions non‐catalytically by binding the Snf7 subunit of the ESCRT‐III complex, which regulates the membrane scission activity of ESCRT‐III. The catalytic and noncatalytic functions of Doa4 are inhibited through its interaction with the Vps20 subunit of ESCRT‐III. This inhibition is relieved by the Bro1 protein, which binds directly to Vps20.